Comparative analysis of nitrogen content and its influence on actinorhizal nodule and rhizospheric microorganism diversity in three Alnus species - Yuan, Yuwei; Chen, Zhi; Huang, Xin; Wang, Fang; Guo, Hongying; Huang, Zhen; Yang, Hanbo (Frontiers in Microbiology, 2023)
Alnus spp. (alder) are typical nonleguminous nitrogen-fixing trees that have a symbiotic relationship with Frankia. To explore the differences in nitrogen-fixing microorganisms between three alders with different chromosome ploidies, the community structure and compositional diversity of microorganism in root nodules and rhizosphere soil were comparatively analyzed using 16S rRNA and nifH gene sequencing. The nitrogen contents in the root nodules and rhizosphere soil were also determined. The contents of total nitrogen and nitrate nitrogen in the root nodules of the three alders are significantly higher than those in the rhizosphere soils, while the ammonium nitrogen content show the opposite trend. The family, genus, and species levels showed obviously differences between root nodules and rhizosphere soils, while there were no significant differences at the classification level between the three alders.The dominant phyla in the root nodules and rhizosphere soil of the three alders are phylum Actinomycetota and phylum Pseudomonadota, respectively. There are significant differences in the dominant groups in the root nodules and rhizosphere oil of the three alders. The relative abundances in A. glutinosa root nodules are significantly higher than those in A. cremastogyne and A. formosana at the genus and species levels. The diversity of potential nitrogen-fixing microorganism from 16S rRNA and nifH gene data in the A. glutinosa root nodules and rhizosphere This is a provisional file, not the final typeset article soils are all higher than those in A. cremastogyne and A. formosana. The results of functional prediction also showed that the OTUs for nitrogen fixation, nitrate respiration, and ureolysis in A. glutinosa root nodules are higher than those in the other two alders. The total nitrogen content mostly affects the Frankia community. Overall, there are significant differences in the community composition and structure of potential nitrogen-fixing microorganism in the root nodules and rhizosphere soils between the three alders. A. glutinosa showed a relatively stronger nitrogen fixation capacity than A. formosana and A. cremastogyne. The results help elucidates how the community structure and nitrogen-fixing ability of potential nitrogen-fixing microorganism differ between alder species and serve as a reference for applying Frankia to alder plantations.